The Integration of Realistic Episodic Memories Relies on Different Working Memory Processes: Evidence from Virtual Navigation - Plancher, Gaën (Front Psychol, 2018)
Memory is one of the most important cognitive functions in a person’s life as it is essential for recalling personal memories and performing many everyday tasks. Although a huge number of studies have been conducted in the field, only a few of them investigated memory in realistic situations, due to methodological issues. The various tools that have been developed using virtual environments (VEs) have gained popularity in cognitive psychology and neuropsychology because they enable to create naturalistic and controlled situations, and are thus particularly adapted to the study of episodic memory (EM), for which an ecological evaluation is of prime importance. EM is the conscious recollection of personal events combined with their phenomenological and spatiotemporal encoding contexts. Using an original paradigm in a VE, the objective of the present study was to characterize the construction of episodic memories. While the concept of working memory has become central in the understanding of a wide range of cognitive functions, its role in the integration of episodic memories has seldom been assessed in an ecological context. This experiment aimed at filling this gap by studying how EM is affected by concurrent tasks requiring working memory resources in a realistic situation. Participants navigated in a virtual town and had to memorize as many elements in their spatiotemporal context as they could. During learning, participants had either to perform a concurrent task meant to prevent maintenance through the phonological loop, or a task aimed at preventing maintenance through the visuospatial sketchpad, or no concurrent task. EM was assessed in a recall test performed after learning through various scores measuring the what, where and when of the memories. Results showed that, compared to the control condition with no concurrent task, the prevention of maintenance through the phonological loop had a deleterious impact only on the encoding of central elements. By contrast, the prevention of visuo-spatial maintenance interfered both with the encoding of the temporal context and with the binding. These results suggest that the integration of realistic episodic memories relies on different working memory processes that depend on the nature of the traces.